2019
DOI: 10.1080/00909882.2019.1587176
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based digital literacy class for older, low-income African-American adults

Abstract: Evidence-based digital literacy class for low-income African-American older adults. Journal of Applied Communication Research, 47(2), 130-152.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(92 citation statements)
references
References 30 publications
5
82
0
Order By: Relevance
“…Social networks play a critical role in providing assistance, yet availability and approaches to support provision can hamper support outcomes. Although most often family members, especially adult children, are the main source of support, greater access to alternative communitybased support may be an additional source of help for individuals who lack satisfactory options within their own social circles (Seo et al 2019). Additionally, given our findings that older adults can have great ease with solving technologyrelated problems, peer-driven support networks where older adults can offer support to others in need may be an effective approach to providing digital technology guidance.…”
Section: Discussionmentioning
confidence: 96%
“…Social networks play a critical role in providing assistance, yet availability and approaches to support provision can hamper support outcomes. Although most often family members, especially adult children, are the main source of support, greater access to alternative communitybased support may be an additional source of help for individuals who lack satisfactory options within their own social circles (Seo et al 2019). Additionally, given our findings that older adults can have great ease with solving technologyrelated problems, peer-driven support networks where older adults can offer support to others in need may be an effective approach to providing digital technology guidance.…”
Section: Discussionmentioning
confidence: 96%
“…It was recently shown that digital literacy and Internet experience are negatively associated with credibility assessment of online materials, hence it makes Internet users more critic about the content they encounter online (Shen et al, 2019). Indeed, it is the goal of many media literacy programs worldwide to evaluate incoming information (Manzoor, 2018), and evidence exists of the explicit benefit of such programs in the specific context of online information verification (Seo, Erba, Altschwager, & Geana, 2019). As part of digital literacy education, the major focus should be given to the role of peripheral cues on credibility assessment in social networking sites.…”
Section: Discussionmentioning
confidence: 99%
“…Skills barrier: low self-efficacy and mental health challenges. Studies have shown that lack of relevant skills is one of the main reasons for people not using the Internet (Seo et al, 2019;Teltscher, 2018). In this sense, there have been growing calls for technology training for marginalized populations, especially in the wake of the COVID-19 pandemic (Lee, 2020;Reardon, 2020).…”
Section: Precarity and Digital Communication Technologies (Rq1)mentioning
confidence: 99%
“…Self-efficacy refers to an individual's belief in their competence to deal with various situations needed to accomplish desired outcomes (Bandura, 1997). Other studies that examined technology learning of marginalized older adults also showed low levels of self-efficacy among the groups (Gray et al, 2017;Seo et al, 2019). Even within younger generations, self-efficacy tends to be highly associated with technology use with those with higher self-efficacy more likely to actively use digital technologies and participate in social activities online (Seo et al, 2014).…”
Section: Precarity and Digital Communication Technologies (Rq1)mentioning
confidence: 99%
See 1 more Smart Citation